Antioxidant and Antibacterial Activities Evaluation, Phytochemical Characterisation of Rhizome from Angiopteris helferiana and Barks from Saurauia fasciculata in Nepal - Ram Kishor Yadav; Akriti Dhakal; Kalpana Timilsina; Priyanka Shrestha; Sandesh Poudel; Sindhu KC; Prabhat Kumar Jha; Rekha Bhandari; Khem Raj Joshi (The Scientific World Journal)
Ethnomedicinally, more than 2000 plants were found to be used in Nepal. Among them, the red colored rhizome of Angiopteris helferiana and the bark of Saurauia fasciculata have been used widely to treat muscle fatigue, bone pain, fever, postpartum hemorrhage, and thirst by healers in Kaski and Tanahun districts, Nepal. However, scientific evidence towards their traditional uses is lacking till December, 2023. Therefore, we report the phytochemicals, total phenolic content (TPC), total flavonoid content (TFC), total carbohydrate content (TCC), antioxidant and antibacterial activities of A. helferiana and S. fasciculata extracts. Phytochemical analysis indicated that A. helferiana and S. fasciculata extracts were potential sources of chemicals such as phenols, flavonoids, tannins, terpenoids, saponins, and carbohydrates. The TPC, TFC, and TCC of extracts were determined by using an ultraviolet visible spectrophotometer. Among the extracts tested, A. helferiana extracts showed the highest phenolic and carbohydrate contents of 208.33 ± 12.96 mg of gallic acid equivalent/g and 564.16 ± 2.92 mg of D-glucose equivalent/g of dry extract, respectively. Similarly, S. fasciculata revealed the highest flavonoid content of 30.35 ± 0.1 mg quercetin equivalent/g of dry extract. The extract of A. helferiana and S. fasciculata exhibited potent antioxidant activity by scavenging 2,2-diphenyl-1-picrylhydrazyl radicals with an IC50 of 25.9 µg/ml and 31.07 µg/ml, respectively. The antibacterial activity of the A. helferiana and S. fasciculata extract against Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli was determined using an agar-well diffusion protocol that revealed the potential antibacterial activity of A. helferiana against E. coli. The present study will help validate the traditional uses of A. helferiana rhizomes and S. fasciculata barks as a healing medicine and inspire the researcher towards further research, development, and formulation.